2011
DOI: 10.3184/095422911x13103699236851
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and bioavailability of zinc in amended sediments

Abstract: The speciation and bioavailability of zinc (Zn) in smelter-contaminated sediments were investigated as a function of phosphate (apatite) and organic amendment loading rate. Zinc species identified in preamendment sediment were zinc hydroxide-like phases, sphalerite, and zinc sorbed to an iron oxide via X-ray adsorption near edge structure (XANES) spectroscopy. Four months after adding the amendments to the contaminated sediment, hopeite, a Zn phosphate mineral, was identified indicating phosphate was binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Synchrotron‐based μ‐XRD analyses of these same POIs confirmed the presence of willemite and hemimorphite, which are both Zn silicate minerals. Other studies using EXAFS discovered that Zn primarily exists as willemite, hemimorphite, gahnite, franklinite, and sphalerite, and incorporated into the interlayers of phyllosilicate minerals (i.e., LDH phases) in smelter‐contaminated environments (Isaure et al, 2005; Manceau et al, 2000; Nachtegaal et al, 2005; Roberts et al, 2002; Sarret et al, 2004; Scheinost et al, 2002; Williams et al, 2011). The minerals willemite, hemimorphite, franklinite, and gahnite are all high‐temperature Zn minerals that were likely formed during the smelting process, which causes them to be highly crystalline and easily identified by XRD (Manceau et al, 2000; Nachtegaal et al, 2005; Roberts et al, 2002; Williams et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrotron‐based μ‐XRD analyses of these same POIs confirmed the presence of willemite and hemimorphite, which are both Zn silicate minerals. Other studies using EXAFS discovered that Zn primarily exists as willemite, hemimorphite, gahnite, franklinite, and sphalerite, and incorporated into the interlayers of phyllosilicate minerals (i.e., LDH phases) in smelter‐contaminated environments (Isaure et al, 2005; Manceau et al, 2000; Nachtegaal et al, 2005; Roberts et al, 2002; Sarret et al, 2004; Scheinost et al, 2002; Williams et al, 2011). The minerals willemite, hemimorphite, franklinite, and gahnite are all high‐temperature Zn minerals that were likely formed during the smelting process, which causes them to be highly crystalline and easily identified by XRD (Manceau et al, 2000; Nachtegaal et al, 2005; Roberts et al, 2002; Williams et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The use of P to immobilize Pb in soils, presumably through the formation of Pb phosphates such as pyromorphite, has been extensively studied (Cao et al, 2003; Cotter‐Howells, 1996; Cotter‐Howells and Caporn, 1996; Cotter‐Howells et al, 1994; Hettiarachchi and Pierzynski, 2004; Hettiarachchi et al, 2000; Kilgour et al, 2008; Scheckel and Ryan, 2004; Yoon et al, 2007). Immobilization of Zn has been researched less, although it has been included in a few studies because of its close geologic association with Pb (Cao et al, 2003; Cotter‐Howells and Caporn, 1996; Hettiarachchi and Pierzynski, 2002; Ma et al, 1994; McGowen et al, 2001; Panfili et al, 2005; Williams et al, 2011). Under normal environmental conditions, it is proposed that Zn phosphates will form when P is added (Nriagu, 1984).…”
mentioning
confidence: 99%
“…Investigations of phosphate amendments on co-contaminated soils are limited and none of them examined bioavailability of the co-contaminants. Zinc and Cd interactions with phosphate amendments were noted (Agbenin, 1998;Barrow, 1987;Basta et al, 2001Basta et al, , 2005Brown et al, 2004;Cao et al, 2004;Chen et al, 2007;McGowen et al, 2001;Sauve et al, 1998;Williams et al, 2011;Xenidis et al, 1999;Zwonitzer et al, 2003), showing that phosphate minerals of Zn and Cd potentially form resulting in reduced extractability and toxicity. However, there is some evidence that phosphate amendments that significantly lower the soil pH enhance Zn mobility and affect Zn speciation (Baker et al, 2012).…”
Section: Co-contaminant Interactions That Are Of Potential Concernmentioning
confidence: 93%
“…The findings of several studies indicated that phosphate minerals of Zn and Cd may have been formed, resulting in reduced extractability and toxicity (Brown et al, 2005;Chen et al, 2007;Kumpiene et al, 2008;Williams et al, 2011), and there were some evidences that phosphate amendments significantly lowered the soil pH and affected Zn speciation and enhanced Zn mobility (Baker et al, 2012). For multiple metals pollution, some investigations have shown that Zn and Cd could interact with phosphate amendments simultaneously, which led to the reduction of extractability and toxicity (Chen et al, 2007;Williams et al, 2011). However, other studies have shown only a slightly reduced Zn solution concentration after application of phosphoric acid, while Pb, Cd and Cu concentrations were simultaneously decreased five-to tenfold (Impellitteri, 2005).…”
Section: Introductionmentioning
confidence: 99%